The landscape of pregnancy and prepregnancy cohorts: a scoping review - Maxwell, Lauren; Gilyan, Regina; Chavan, Sayali Arvind; Akter, Shaila; Bhatt, Mahir; Cunningham, Solveig A.; Jänisch, Thomas (BMC pregnancy and childbirth, 2025)
Background: Recent research in life course epidemiology has demonstrated the importance of evaluating how prepregnancy and pregnancy exposures affect later life developmental outcomes. In this scoping review, we identified and described completed or ongoing pregnancy and prepregnancy cohorts to assess gaps in the maternal exposures and child outcomes measured in these initiatives and inform future research investments. Methods: We developed a systematic search that included text and MeSH terms and was tailored for four biomedical citation databases. We applied the Arskey and O’Malley scoping review methodology. We selected a scoping review methodology to provide a comprehensive overview of pregnancy and prepregnancy cohorts and their characteristics. Two reviewers independently conducted the title, abstract, full-text screening, and data charting; a third reviewer resolved discrepancies. The results were summarised in narrative form. Results: We reviewed 147 manuscripts that presented findings from 56 pregnancy and two prepregnancy cohorts, 23 of which were ongoing. Half of the pregnancy cohorts were based in Europe. The most commonly described maternal exposures were nutrition, anthropometric measures, non-communicable diseases (NCDs), and demographic factors. Children’s mental, behavioural, neurodevelopmental, and physical outcomes were the most commonly measured outcomes. Fewer studies evaluated infectious disease, biomarkers, and environmental or workplace exposures. No cohorts examined vaccine or climate-related exposures during pregnancy. About half of the cohorts collected samples from pregnant women or the fetus, and a third from children, with blood being the most common sample type. Most studies did not indicate how data or samples could be accessed. Conclusions: This comprehensive overview of pregnancy and prepregnancy cohorts provides a foundation for cross-cohort coordination. Infectious disease, vaccine, environmental, and climate-related exposures and microbiome, immune function, and economic outcomes remain underrepresented in pregnancy and prepregnancy cohorts. Ethics and dissemination: This scoping review summarises findings from existing publications in peer-reviewed journals and did not require ethics review.